Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Variability in cadmium stress and accumulation in quinoa: Potential role of crop domestication and selection in mediating differences in resilience and uptake - Alejandro Rodriguez-Sanchez; Martha Jimenez-Castaneda; Timothy Filley; David Brenner; Dennis Macedo; Victor H. Casa; Lori Hoagland (Science of The Total Environment, 2026)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Invasive Japanese beetle (Popillia japonica Newman) larvae alter structure and carbon distribution in infested surface soil - Gordon R. MacLeod; Douglas S. Richmond; Timothy R. Filley (Science of The Total Environment, 2024)

Seasonal differences in trace metal concentrations in the major rivers of the hyper-arid southwestern Andes basins of Peru - Alexander Ccanccapa-Cartagena; Francisco D. Chavez-Gonzales; Betty Paredes; Corina Vera; Guillermo Gutierrez; Roland Valencia; Ana Lucia Paz Alcázar; Nadezhda N. Zyaykina; Timothy R. Filley; Chad T. Jafvert (Journal of Environmental Management, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Carrot genotypes differentially alter soil bacterial communities and decomposition of plant residue in soil - Narda J. Triviño; Alejandro Rodriguez-Sanchez; Timothy Filley; James J. Camberato; Micaela Colley; Phillip Simon; Lori Hoagland (Plant and Soil, 2023)
Purpose Farmers need alternative approaches to manage nitrogen (N) that meet crop needs while reducing loss to the environment. Identifying crop genotypes that promote decomposition of organic materials and understanding the potential mechanisms responsible could help address this challenge. Consequently, we aimed to 1) determine whether carrot genotypes differ in their potential to facilitate organic matter decomposition in soil, and 2) identify bacterial taxa that are stimulated by carrot roots, and thus could play a role in these processes. Methods We grew five genotypes expected to differ in N use efficiency in a nutrient-poor soil amended with 15 N-enriched corn residue, tracked changes in carbon (C) and N pools, quantified microbial activity and bacterial community composition, and predicted the potential expression of microbial genes involved in soil C and N cycles. Results Experimental genotype 8503 had the greatest capacity to promote decomposition of corn residues. This genotype had the highest % of N from the corn residue in its taproots and on average, promoted higher b-glucosidase activity in soils. Distinct bacterial communities from the families Micromonosporaceae , Chromatiaceae , and Rhodospirillaceae were also enriched in the soils of genotypes like 8503 that were most effective in obtaining N from the corn residue, and this was correlated with greater potential expression of genes responsible for β-glucosidase and nitrification activity. Conclusions Carrot genotypes do differ in their potential to alter soil bacterial communities and stimulate microbially-mediated decomposition of organic materials indicating that it may be possible to begin selecting for this important trait.

Storm pulse responses of fluvial organic carbon to seasonal source supply and transport controls in a midwestern agricultural watershed - Tingyu Hou; Neal E. Blair; A.N. Thanos Papanicolaou; Timothy R. Filley (Science of The Total Environment, 2023)

Warming yields distinct accumulation patterns of microbial residues in dry and wet alpine grasslands on the Qinghai-Tibetan Plateau - Xueli Ding; Shengyun Chen; Bin Zhang; Hongbo He; Timothy R. Filley; William R. Horwath (Biology and Fertility of Soils, 2020)

Conversion of grassland into cropland affects microbial residue carbon retention in both surface and subsurface soils of a temperate agroecosystem - Xueli Ding; Bin Zhang; Zhanbo Wei; Hongbo He; Timothy R. Filley (Biology and Fertility of Soils, 2020)

Changes of microbial residues after wetland cultivation and restoration - Xueli Ding; Bin Zhang; Timothy R. Filley; Chunjie Tian; Xudong Zhang; Hongbo He (Biology and Fertility of Soils, 2019)

Litter quality, dispersal and invasion drive earthworm community dynamics and forest soil development - Katalin Szlavecz; Chih-Han Chang; Michael J. Bernard; Scott L. Pitz; Lijun Xia; Yini Ma; Melissa K. McCormick; Timothy Filley; Stephanie A. Yarwood; Ian D. Yesilonis; Csaba Csuzdi (Oecologia, 2018)

Long-term changes in land use impact the accumulation of microbial residues in the particle-size fractions of a Mollisol - Xueli Ding; Yunfa Qiao; Timothy Filley; Haiying Wang; Xinxin Lü; Bin Zhang; Jingkuan Wang (Biology and Fertility of Soils, 2017)

Patterns of woody plant-derived soil carbon losses and persistence after brush management in a semi-arid grassland - Jennie DeMarco; Timothy Filley; Heather L. Throop (Plant and Soil, 2016)

Belowground competition among invading detritivores - Chih‐Han Chang; Katalin Szlavecz; Timothy Filley; Jeffrey S. Buyer; Michael J. Bernard; Scott L. Pitz (Ecology, 2016)
The factors regulating soil animal communities are poorly understood. Current theory favors niche complementarity and facilitation over competition as the primary forms of non‐trophic interspecific interaction in soil fauna; however, competition has frequently been suggested as an important community‐structuring factor in earthworms, ecosystem engineers that influence belowground processes. To date, direct evidence of competition in earthworms is lacking due to the difficulty inherent in identifying a limiting resource for saprophagous animals. In the present study, we offer the first direct evidence of interspecific competition for food in this dominant soil detritivore group by combining field observations with laboratory mesocosm experiments using 13 C and 15 N double‐enriched leaf litter to track consumption patterns. In our experiments, the Asian invasive species Amynthas hilgendorfi was a dominant competitor for leaf litter against two European species currently invading the temperate deciduous forests in North America. This competitive advantage may account for recent invasion success of A. hilgendorfi in forests with established populations of European species, and we hypothesize that specific phenological differences play an important role in determining the outcome of the belowground competition. In contrast, Eisenoides lonnbergi , a common native species in the Eastern United States, occupied a unique trophic position with limited interactions with other species, which may contribute to its persistence in habitats dominated by invasive species. Furthermore, our results supported neither the hypothesis that facilitation occurs between species of different functional groups nor the hypothesis that species in the same group exhibit functional equivalency in C and N translocation in the soil. We propose that species identity is a more powerful approach to understand earthworm invasion and its impacts on belowground processes.

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Coupled response of soil carbon and nitrogen pools and enzyme activities to nitrogen and water addition in a semi-arid grassland of Inner Mongolia - Ruzhen Wang; Timothy R. Filley; Zhuwen Xu; Xue Wang; Mai-He Li; Yuge Zhang; Wentao Luo; Yong Jiang (Plant and Soil, 2014)

Ecosystem effects of non-native earthworms in Mid-Atlantic deciduous forests - Katalin Szlavecz; Melissa McCormick; Lijun Xia; Jaclyn Saunders; Taylan Morcol; Dennis Whigham; Timothy Filley; Csaba Csuzdi (Biological Invasions, 2011)

Old and stable soil organic matter is not necessarily chemically recalcitrant: implications for modeling concepts and temperature sensitivity - MARKUS KLEBER; PETER S. NICO; ALAIN PLANTE; TIMOTHY FILLEY; MARC KRAMER; CHRISTOPHER SWANSTON; PHILLIP SOLLINS (Global Change Biology, 2011)
Soil carbon turnover models generally divide soil carbon into pools with varying intrinsic decomposition rates. Although these decomposition rates are modified by factors such as temperature, texture, and moisture, they are rationalized by assuming chemical structure is a primary controller of decomposition. In the current work, we use near edge X‐ray absorption fine structure (NEXAFS) spectroscopy in combination with differential scanning calorimetry (DSC) and alkaline cupric oxide (CuO) oxidation to explore this assumption. Specifically, we examined material from the 2.3–2.6 kg L −1 density fraction of three soils of different type (Oxisol, Alfisol, Inceptisol). The density fraction with the youngest 14 C age (Oxisol, 107 years) showed the highest relative abundance of aromatic groups and the lowest O ‐alkyl C/aromatic C ratio as determined by NEXAFS. Conversely, the fraction with the oldest C (Inceptisol, 680 years) had the lowest relative abundance of aromatic groups and highest O ‐alkyl C/aromatic C ratio. This sample also had the highest proportion of thermally labile materials as measured by DSC, and the highest ratio of substituted fatty acids to lignin phenols as indicated by CuO oxidation. Therefore, the organic matter of the Inceptisol sample, with a 14 C age associated with ‘passive’ pools of carbon (680 years), had the largest proportion of easily metabolizable organic molecules with low thermodynamic stability, whereas the organic matter of the much younger Oxisol sample (107 years) had the highest proportion of supposedly stable organic structures considered more difficult to metabolize. Our results demonstrate that C age is not necessarily related to molecular structure or thermodynamic stability, and we suggest that soil carbon models would benefit from viewing turnover rate as codetermined by the interaction between substrates, microbial actors, and abiotic driving variables. Furthermore, assuming that old carbon is composed of complex or ‘recalcitrant’ compounds will erroneously attribute a greater temperature sensitivity to those materials than they may actually possess.

Biomimetic oxidative treatment of spruce wood studied by pyrolysis–molecular beam mass spectrometry coupled with multivariate analysis and 13C-labeled tetramethylammonium hydroxide thermochemolysis: implications for fungal degradation of wood - Valdeir Arantes; Yuhui Qian; Stephen S. Kelley; Adriane M. F. Milagres; Timothy R. Filley; Jody Jellison; Barry Goodell (JBIC Journal of Biological Inorganic Chemistry, 2009)

Sources of plant‐derived carbon and stability of organic matter in soil: implications for global change - SUSAN E. CROW; KATE LAJTHA; TIMOTHY R. FILLEY; CHRISTOPHER W. SWANSTON; RICHARD D. BOWDEN; BRUCE A. CALDWELL (Global Change Biology, 2009)
Alterations in forest productivity and changes in the relative proportion of above‐ and belowground biomass may have nonlinear effects on soil organic matter (SOM) storage. To study the influence of plant litter inputs on SOM accumulation, the Detritus Input Removal and Transfer (DIRT) Experiment continuously alters above‐ and belowground plant inputs to soil by a combination of trenching, screening, and litter addition. Here, we used biogeochemical indicators [i.e., cupric oxide extractable lignin‐derived phenols and suberin/cutin‐derived substituted fatty acids (SFA)] to identify the dominant sources of plant biopolymers in SOM and various measures [i.e., soil density fractionation, laboratory incubation, and radiocarbon‐based mean residence time (MRT)] to assess the stability of SOM in two contrasting forests within the DIRT Experiment: an aggrading deciduous forest and an old‐growth coniferous forest. In the deciduous forest, removal of both above‐ and belowground inputs increased the total amount of SFA over threefold compared with the control, and shifted the SFA signature towards a root‐dominated source. Concurrently, light fraction MRT increased by 101 years and C mineralization during incubation decreased compared with the control. Together, these data suggest that root‐derived aliphatic compounds are a source of SOM with greater relative stability than leaf inputs at this site. In the coniferous forest, roots were an important source of soil lignin‐derived phenols but needle‐derived, rather than root‐derived, aliphatic compounds were preferentially preserved in soil. Fresh wood additions elevated the amount of soil C recovered as light fraction material but also elevated mineralization during incubation compared with other DIRT treatments, suggesting that not all of the added soil C is directly stabilized. Aboveground needle litter additions, which are more N‐rich than wood debris, resulted in accelerated mineralization of previously stored soil carbon. In summary, our work demonstrates that the dominant plant sources of SOM differed substantially between forest types. Furthermore, inputs to and losses from soil C pools likely will not be altered uniformly by changes in litter input rates.

Fungal diversity and deterioration in mummified woods from the ad Astra Ice Cap region in the Canadian High Arctic - Joel A. Jurgens; Robert A. Blanchette; Timothy R. Filley (Polar Biology, 2009)